Priorities of Realization of the State Youth Policy in the Orel Region - E. N. Malik; V. V. Sokolov (Управленческое консультирование)
In article authors the priority directions of carrying out the state youth policy at the regional level reveal. The attention is focused on a subject role of the younger generation in formation of youth policy in the Oryol region. Modern socio-political practicians objectively indicate developments of innovative mechanisms of realization of regional youth policy the need. Measures of increase in efficiency of realization of the state youth policy in the Oryol region are formulated, considering regional specifics. The offer on creation the Center of professional diagnostics and quality of regional youth policy is proved.